2006
DOI: 10.1097/00005721-200607000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Maternal Outcomes in Women With Asthma

Abstract: As adverse maternal outcomes for women with asthma were higher in minorities, and as minorities have traditionally had more barriers to healthcare, the study results indicate that more effort needs to be made to educate nurses, consumers, and government officials about the potential adverse maternal outcomes of asthma during pregnancy. Public awareness may assist in overcoming the barriers to healthcare experienced by minorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…These data suggest that increased asthma severity may increase the risk of a preterm delivery. Adverse outcomes in asthmatic women are more prevalent in ethnic minorities, as reported in a study that African‐American women with asthma had a greater rate of preterm delivery than Caucasian American women with asthma; 18 this may be a confounder in the previously mentioned study by the Schatz group where more than half of the participants were African Americans 6 . Overall, African‐American women have a higher rate of preterm delivery than any other ethnic group in the USA 19 .…”
Section: Discussionmentioning
confidence: 90%
“…These data suggest that increased asthma severity may increase the risk of a preterm delivery. Adverse outcomes in asthmatic women are more prevalent in ethnic minorities, as reported in a study that African‐American women with asthma had a greater rate of preterm delivery than Caucasian American women with asthma; 18 this may be a confounder in the previously mentioned study by the Schatz group where more than half of the participants were African Americans 6 . Overall, African‐American women have a higher rate of preterm delivery than any other ethnic group in the USA 19 .…”
Section: Discussionmentioning
confidence: 90%
“…These risks may be magnified if maternal chronic conditions are not well controlled (Cundy, Slee, Gamble, & Neale, 2002; MacMullen, Tymkow, & Shen, 2006; Sibai et al, 2000). Women of low socioeconomic status may therefore be at particular risk if they experience barriers to care, such as lack of health care coverage, inability to purchase maintenance medications, access to transportation, and related issues.…”
Section: Background and Significancementioning
confidence: 99%
“…In general, compared to data on asthmatic women from the National Inpatient Sample (NIS), we observed higher prevalence for some obstetric complications including gestational diabetes (Asian/Pacific Islanders 11.3 vs 7.2%), preeclampsia (Whites 5.3 vs 1.6%), PROM (Hispanic 8.2 vs 2.9%) and postpartum hemorrhage (Whites 8.7 vs 2.7%) [12]. The increased rates may be due to differences in the study design and population.…”
Section: Discussionmentioning
confidence: 86%
“…To the best of our knowledge, our study is the first to investigate the joint effects of maternal asthma by maternal race/ethnicity on the odds of obstetric and neonatal complications. One prior study that investigated health disparities in maternal asthma used White women as the comparison group instead of assessing the within group difference between racial/ethnic groups [12]. We also observed that asthma prevalence is found to vary widely across racial/ethnic groups and we decided to explore the impact maternal asthma had on the within-group risk of obstetric and neonatal complications examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation